Genesis 9, Noah’s Covenants and Jewish Theology of Religions - Goshen-Gottstein, Alon (Studies in Christian-Jewish Relations, 2023)
Genesis 9 plays an important role in contemporary Jewish theology of religions. The covenant with Noah is understood as the universal covenant, providing a balance to the particularity of the covenant with Abraham. Such an understanding is found in the works of Jonathan Sacks, Irving Greenberg, and Jon Levenson. This article offers a novel reading of Genesis 9 as a covenant of no-harm, in which both parties commit to avoid inflicting harm upon one another. It introduces a novel typology to covenant studies and undermines our ability to read Genesis 9 in line with the covenants with Abraham and Israel at Sinai. Beyond the contribution to the theological discussion, the article raises the question of the impact of biblical interpretation on theology. The final part of the article offers an alternative reading of the theological import of Noah’s covenant. It is as powerful creator that God is encountered in Genesis 9, rather than as relational partner. If one does not enter into relationship with God, one can at least know him, and the covenant of no harm becomes a means of knowing God.